Influences causing variations in butter fat production - Griffing, John Bernice (My University, 1904)
Introduction: It can be easily seen that where a record of the amount of milk produced by a dairy herd is kept, that there are variations in the quantity more or less marked due to changes in the weather. During very cold weather the quantity is less than in weather with moderate temperature, while a decrease may be noted after storms or other infavorable conditions. The majority of dairymen, however, are not concerned directly with the quantity of milk, but with the quantity of butter fat produced. The question then arises: in what manner is the test, percent of butter fat in the milk, affected by changes in the weather and other external conditions.
Influences affecting the production of butter fat in dairy cows
Citation: Griffing, John Bernice. Influences causing variations in butter fat production. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Butter Fat Production; Data Collection; Agriculture; Food Processing; Theses